Valoración del potencial de harvesting de energía en los accesos vehiculares al Campus San Cayetano de la UTPL en la ciudad de Loja. - Campoverde Muñoz, María Nathaly (2014)
The process of assessment of the potential of harvesting energy on San Cayetano UTPL Campus driveways of Loja’s city is explained. It begins from evaluation of experimental energy harvesting system discharge on driveways designed for its implementation on San Cayetano UTPL Campus. The results obtained of the quantification of potential energy harvesting richness on campus driveways are described. The process of design of a monitoring node of the potential of catchable kinetic energy from vehicular traffic of Paris street is specified. And, finally the methodology and procedures used for the potential of catchable kinetic energy simulation on driveways are explained.